Geopolymer artificial aggregate and preparation method thereof
By mixing phosphogypsum with treatment agent and reinforcement, spray forming and maintenance, a geopolymer artificial aggregate with excellent mechanical properties was prepared, which solved the problem of insufficient utilization rate and mechanical properties of phosphogypsum, and realized Low-cost and efficient resource utilization of industrial solid waste.
Patent Information
- Application Number
- CN202411543090.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art has failed to effectively improve the utilization rate of phosphogypsum and the mechanical properties of geopolymer materials, and the preparation method is high, with low early strength and poor toughness, which limits the resource utilization of industrial solid waste.
By mixing the broken and broken phosphogypsum with the treatment agent, combining reinforcement and auxiliary agent, spraying and molding, and performing specific maintenance, a geopolymer artificial aggregate with excellent mechanical properties is prepared, and dispersible glue powder is used. Solution improves tensile strength and toughness.
The high utilization rate and low cost of phosphogypsum were achieved to prepare lightweight polymer artificial aggregates, and the strength skeleton was formed in the early stage, overcoming the problems of low strength and poor toughness in the early stage, and meeting the "Light Aggregate and its Test Methods" (GB/T 17431) performance requirements.
Smart Images

Figure CN119263673A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of resource utilization of industrial solid waste, and in particular to a geopolymer artificial aggregate and a preparation method thereof. Background Art
[0002] Industrial solid waste refers to various waste residues discharged into the environment during industrial production. At present, the comprehensive utilization rate of phosphogypsum is relatively low both at home and abroad, and most of the untreated phosphogypsum is mainly stored. However, the large-scale storage of industrial solid waste has a series of problems such as land resource occupation, capital consumption, and environmental pollution. Therefore, it is urgent to further explore ways to utilize industrial solid waste resources and expand the utilization of industrial solid waste in various fields.
[0003] Natural aggregate is one of the materials used in the construction process of urbanization projects. This will lead to the consumption of natural resources and have an adverse impact on environmental sustainability. Therefore, using industrial solid waste to prepare artificial aggregates to replace natural aggregates can solve the problem of large-scale mining of natural aggregates and promote the sustainable development of industry, which has significant economic, environmental and social benefits.
[0004] Geopolymer materials (geopolymers) are made from industrial waste residues such as granulated blast furnace slag, fly ash, phosphorus slag, carbide slag, etc. The coagulation and hardening process of geopolymer materials is a reaction process in which the silicon-oxygen bonds and aluminum-oxygen bonds in the raw materials are broken and then reorganized under the action of alkaline catalysts. However, this coagulation and hardening process is slow, resulting in low early strength. In addition, the matrix material of geopolymer materials has defects such as low tensile strength and poor toughness. These problems seriously restrict the preparation and promotion of geopolymer artificial aggregates.
[0005] Patent application document CN 117229025 A discloses a phosphogypsum cementitious material modifier and its preparation method, phosphogypsum cementitious material, and phosphogypsum lightweight aggregate. The prior art uses the alkali-induced coagulation and hardening principle in geopolymer materials to calcine phosphogypsum, so that phosphogypsum has early strength performance. However, the calcination cost is high, which is not conducive to promotion and application.
[0006] Patent application document CN 113956011 B discloses a semi-hydrated phosphogypsum-based filling aggregate and a preparation method thereof. This prior art has some shortcomings: 1. The phosphogypsum is not pretreated; 2. This invention is only for filling aggregates and is not suitable for use in other building materials, such as concrete, because its softening coefficient does not meet the standard; 3. The curing method is natural air drying, without better curing.
[0007] Patent application document CN 115677306 B discloses a green artificial aggregate based on phosphogypsum and a preparation method thereof. The shortcomings of this prior art are: 1. The phosphogypsum is pretreated at 120 to 160°C, which increases production costs; 2. It does not involve pretreatment of the phosphogypsum, such as breaking up and alkaline modification of the phosphogypsum, so that the phosphogypsum can achieve the performance as a lightweight aggregate raw material; 3. The physical and mechanical properties of the prepared phosphogypsum lightweight aggregate need to be improved.
[0008] Patent application document CN 117229025 A discloses a phosphogypsum cementitious material modifier and its preparation method, phosphogypsum cementitious material, and phosphogypsum lightweight aggregate. This prior art uses the following raw materials: 50-100 parts of dehydrated phase of persulfated phosphogypsum aggregate waste powder, 0-10 parts of fly ash, 5-20 parts of metakaolin, 0-10 parts of silica fume, 4-12 parts of quicklime, and 0-0.01 parts of gypsum retarder. The shortcomings are: 1. The phosphogypsum is pretreated at 100-200°C, which increases the production cost; 2. The pretreatment of phosphogypsum is not involved, such as breaking up and alkaline modification of phosphogypsum, and there is no better treatment to make the phosphogypsum reach the performance of lightweight aggregate raw material.
[0009] It can be seen that the prior art fails to take into account the physical and chemical properties of phosphogypsum itself, and performs certain pretreatment, so that a large amount of additives are added to the preparation method. This not only increases the production cost of phosphogypsum-related materials, but also reduces the utilization rate of phosphogypsum. In addition, the mechanical properties of the prepared material need to be improved. Summary of the invention
[0010] In view of this, the technical problem to be solved by the present invention is to provide a geopolymer artificial aggregate and a preparation method thereof. The preparation method provided by the present invention has simple and easily available raw materials, low cost, convenient operation, high utilization rate of phosphogypsum, and the prepared geopolymer artificial aggregate is lightweight and has excellent mechanical properties.
[0011] The present invention provides a method for preparing geopolymer artificial aggregate, comprising the following steps:
[0012] S1) mixing the crushed and dispersed phosphogypsum and the treating agent to obtain a phosphogypsum treated material;
[0013] The reinforcing agent and the auxiliary agent are mixed to obtain a geopolymer mixture;
[0014] S2) mixing the phosphogypsum treated material and the geopolymer mixture, and then molding; during the molding process, spraying a dispersible rubber powder solution;
[0015] S3) curing the formed material to obtain geopolymer artificial aggregate.
[0016] Preferably, the phosphogypsum includes at least one of dihydrate phosphogypsum and hemihydrate phosphogypsum;
[0017] The treatment agent includes at least one of lime, carbide slag and cement;
[0018] The mass ratio of the crushed and dispersed phosphogypsum to the treating agent is 100:0.5-2.
[0019] Preferably, the pH value of the phosphogypsum treated material is 8-12, and the specific surface area is 100-400cm 2 / g.
[0020] Preferably, the reinforcing agent comprises cement and / or lime;
[0021] The auxiliary agent includes at least one of industrial waste fly ash, slag and phosphorus slag powder;
[0022] The mass ratio of the reinforcing agent to the auxiliary agent is 5-50:50-95.
[0023] Preferably, the specific surface area of the geopolymer mixture is 200 to 400 cm 2 / g;
[0024] The mass ratio of the phosphogypsum treated material to the geopolymer mixture is 50-90:10-50.
[0025] Preferably, the forming is carried out in a disc granulator; the disc inclination angle of the disc granulator is 50° to 80°.
[0026] Preferably, the mass concentration of the dispersible rubber powder solution is 20% to 45%;
[0027] The mass ratio of the mixed material after the phosphogypsum treated material and the geopolymer mixed material is 90-105:0-10 to the dispersible rubber powder solution, and the mass of the dispersible rubber powder solution is not zero.
[0028] Preferably, the particle size of the material after molding is 4.75-26.5 mm, and the water content is 15%-23%.
[0029] Preferably, the curing temperature is 10-30° C., the humidity is 50%-90%; and the curing period is 7-28 days.
[0030] After the curing, storing;
[0031] The storage temperature is 10-30° C., and the humidity is 50%-90%.
[0032] The present invention also provides a geopolymer artificial aggregate prepared by the preparation method described above.
[0033] The present invention provides a method for preparing geopolymer artificial aggregate, comprising the following steps: S1) mixing crushed and broken phosphogypsum and a treating agent to obtain phosphogypsum treated material; mixing a reinforcing agent and an auxiliary agent to obtain a geopolymer mixture; S2) mixing the phosphogypsum treated material and the geopolymer mixture, and then molding; during the molding process, spraying a dispersible rubber powder solution; S3) curing the molded material to obtain geopolymer artificial aggregate. The geopolymer artificial aggregate prepared by the present invention can absorb a large amount of industrial waste residue (such as fly ash, slag, phosphorus slag, carbide slag, phosphogypsum, etc.), providing a favorable way to improve the comprehensive utilization rate of industrial solid waste. The geopolymer artificial aggregate prepared by the present invention has the properties of light weight and good mechanical properties. The phosphogypsum has a fast hydration rate and can form an early strength skeleton, which cleverly overcomes the low early strength of the geopolymer. The dispersible rubber powder can improve the defects of low tensile strength and poor toughness of ordinary geopolymer matrix, and play a role in crack prevention and toughening. The various raw material components can be well matched with each other, and the specific process steps are combined to make the obtained geopolymer artificial aggregate have better mechanical properties. The experimental results show that the performance of the prepared geopolymer artificial aggregate can meet the requirements of "Lightweight Aggregate and Its Test Methods" (GB / T 17431). BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0035] Figure 1 The present invention provides a process flow chart for preparing geopolymer artificial aggregates according to an embodiment of the present invention. DETAILED DESCRIPTION
[0036] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0037] The present invention provides a method for preparing geopolymer artificial aggregate, comprising the following steps:
[0038] S1) mixing the crushed and dispersed phosphogypsum and the treating agent to obtain a phosphogypsum treated material;
[0039] The reinforcing agent and the auxiliary agent are mixed to obtain a geopolymer mixture;
[0040] S2) mixing the phosphogypsum treated material and the geopolymer mixture, and then molding; during the molding process, spraying a dispersible rubber powder solution;
[0041] S3) curing the formed material to obtain geopolymer artificial aggregate.
[0042] Regarding step S1):
[0043] The crushed and dispersed phosphogypsum and the treating agent are mixed evenly to obtain the phosphogypsum treated material.
[0044] The phosphogypsum is selected from at least one of dihydrate phosphogypsum and hemihydrate phosphogypsum.
[0045] The particle size of the crushed and dispersed phosphogypsum does not exceed 2.36 mm. The crushing and dispersion is carried out in a double-shaft mixer.
[0046] The treatment agent is selected from at least one of lime, carbide slag and cement. In certain embodiments of the present invention, the treatment agent is lime or cement; or the treatment agent is lime and carbide slag, with a mass ratio of 1:1.
[0047] The mass ratio of the crushed and dispersed phosphogypsum to the treating agent is 100:0.5-2, such as 100:0.5, 100:2.
[0048] The mixing is carried out in a double-shaft mixer.
[0049] The pH value of the phosphogypsum treated material is 8-12, such as 8, 12, 11, 10; the specific surface area is 100-400cm 2 / g, specifically 102.98cm 2 / g, 120.01cm 2 / g, 226.67cm 2 / g, 117.41cm 2 / g.
[0050] In the present invention, the pH value of the phosphogypsum treated material is limited to 8-12 because the soluble phosphorus and fluorine in the phosphogypsum have a great influence on the mechanical strength of the phosphogypsum. When the treatment agent is added to make the pH value of the phosphogypsum treated material 8-12, the mechanical strength of the phosphogypsum is improved to a certain extent. The specific surface area is limited to 100-400cm 2 / g is because: if phosphogypsum exists in the form of large particles, the strength of the geopolymer artificial aggregate samples is uneven and the local performance is poor, resulting in the performance of the geopolymer artificial aggregate failing to meet the requirements of "Light Aggregate and Its Test Methods" (GB / T 17431).
[0051] The reinforcing agent and the auxiliary agent are mixed to obtain a geopolymer mixture.
[0052] The reinforcing agent is selected from cement and / or lime. In certain embodiments, the reinforcing agent is cement or lime; or the reinforcing agent is cement and lime, with a mass ratio of 1:1.
[0053] The auxiliary agent is selected from at least one of industrial waste fly ash, slag and phosphorus slag powder. In some embodiments, the auxiliary agent is slag and fly ash, with a mass ratio of 6:4; or the auxiliary agent is slag or phosphorus slag powder.
[0054] The mass ratio of the reinforcing agent to the auxiliary agent is 5-50:50-95, such as 20:80, 5:95, 50:50.
[0055] The mixing is carried out in a double-shaft screw mixer.
[0056] The specific surface area of the geopolymer mixture is 200 to 400 cm 2 / g, such as 300-400cm 2 / g, specifically 343.56cm 2 / g, 320.40cm 2 / g, 360.12cm 2 / g, 349.47cm 2 / g.
[0057] The specific surface area of the geopolymer mixture is limited to 200-400 cm 2 / g is due to: specific surface area < 200cm 2 / g, its gelling activity is not good, the mechanical strength of geopolymer artificial aggregate does not meet the requirements, and the specific surface area is greater than 400cm 2 / g, although it has good gelling activity, the cost of raw materials is increased, which is not conducive to the promotion and application of geopolymer artificial aggregates.
[0058] Regarding step S2):
[0059] The phosphogypsum treated material and the geopolymer mixture are mixed and then molded; during the molding process, a dispersible rubber powder solution is sprayed.
[0060] The mass ratio of the phosphogypsum treated material to the geopolymer mixture is 50-90:10-50, such as 70:30, 60:40, 90:10.
[0061] The forming is carried out in a disc granulator; the disc inclination angle of the disc granulator is 50° to 80°, such as 60° or 55°.
[0062] The mass concentration of the dispersible rubber powder solution is 20% to 45%, such as 30%.
[0063] The mass ratio of the mixed material after the phosphogypsum treated material and the geopolymer mixed material to the dispersible rubber powder solution is 90-105:0-10, and the mass of the dispersible rubber powder solution is not 0; for example, 90-105:1-3, specifically 90:2, 105:2.
[0064] The particle size of the molded material (geopolymer lightweight aggregate) is 4.75-26.5 mm, and the water content is 15%-23%, such as 17%, 15.06%, and 19.26%.
[0065] The present invention limits the moisture content of the formed material (geopolymer lightweight aggregate) to 15% to 23%, because the hydration process of geopolymer lightweight aggregate requires a certain amount of moisture, and the hydration reaction generates a gelling substance to improve the mechanical properties of the geopolymer lightweight aggregate. If the moisture content is too high, the geopolymer lightweight aggregate will be muddy, and the surface will be seriously powdery after curing, which will not only affect the appearance of the geopolymer lightweight aggregate, but also the mechanical properties will not meet the requirements of "Light Aggregate and Its Test Method" (GB / T 17431). If the moisture content is too low, there is a hidden danger of shrinkage cracks.
[0066] Regarding step S3):
[0067] The formed material is cured to obtain geopolymer artificial aggregate.
[0068] The curing temperature is 10-30°C, such as 20°C, 10°C; the humidity is 50%-90%, such as 90%, 80%, 55%; the curing age is 7-28 days, such as 28 days, 7 days, 15 days.
[0069] After the curing, storage is performed.
[0070] The storage temperature is 10-30° C., such as 20° C., 10° C.; the humidity is 50%-90%, such as 90%, 80%, 55%.
[0071] The curing and storage are both carried out in a stockpile shed.
[0072] The present invention further limits the temperature, humidity and curing age of the curing environment, which helps to improve the performance of geopolymer artificial aggregate.
[0073] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.
[0074] The present invention does not require high-temperature pretreatment of phosphogypsum.
[0075] In the method for preparing the geopolymer artificial aggregate provided by the present invention, no alkali activator (such as water glass or sodium hydroxide) is needed; and no water reducing agent is needed.
[0076] The present invention also provides a geopolymer artificial aggregate prepared by the preparation method described above.
[0077] The geopolymer artificial aggregate prepared by the present invention can absorb a large amount of industrial waste residue (such as fly ash, slag, phosphorus slag, carbide slag, phosphogypsum, etc.), providing a favorable way to improve the comprehensive utilization rate of industrial solid waste. The geopolymer artificial aggregate prepared by the present invention has the properties of light weight and good mechanical properties. The phosphogypsum has a fast hydration rate and can form an early strength skeleton, which cleverly overcomes the low early strength of the geopolymer. The dispersible rubber powder can improve the defects of low tensile strength and poor toughness of ordinary geopolymer matrix, and play a role in crack prevention and toughening. The various raw material components can be well matched with each other, and at the same time, specific process steps are matched, so that the obtained geopolymer artificial aggregate has better mechanical properties. The experimental results show that the performance of the prepared geopolymer artificial aggregate can meet the requirements of "Light Aggregate and Its Test Method" (GB / T17431).
[0078] In order to further illustrate the present invention, a geopolymer artificial aggregate and a preparation method thereof provided by the present invention are described in detail below in conjunction with embodiments, but it should not be construed as limiting the scope of protection of the present invention.
[0079] Example 1
[0080] Use Figure 1 The process flow shown is for preparing geopolymer artificial aggregates:
[0081] 1) Pretreatment of phosphogypsum:
[0082] The phosphogypsum raw material (100 parts by weight of dihydrate phosphogypsum) is crushed and dispersed in a double-shaft mixer (the particle size of the crushed and dispersed phosphogypsum does not exceed 2.36 mm), and is uniformly mixed with 0.5 parts by weight of a treating agent (lime) to obtain a phosphogypsum treated material; the pH value of the phosphogypsum treated material is 8, and the specific surface area is 102.98 cm 2 / g.
[0083] 2) Preparation of geopolymer mixture:
[0084] 20 parts by weight of reinforcing agent (cement) and 80 parts by weight of auxiliary agent (60 parts by weight of slag and 40 parts by weight of fly ash) were added into a double-shaft screw mixer and mixed evenly to obtain a geopolymer mixture with a specific surface area of 343.56 cm 2 / g.
[0085] 3) Dispersible rubber powder incorporation and molding:
[0086] The phosphogypsum treated material and the geopolymer mixture are conveyed to a disc granulator in a mass ratio of 70:30, and the mixture is molded in the disc granulator (the disc inclination angle of the disc granulator is 60°); during the molding process, a dispersible rubber powder solution (mass concentration is 30%) is sprayed, and the mass ratio of the mixture after the phosphogypsum treated material and the geopolymer mixture are evenly mixed to the dispersible rubber powder solution is 90:2; finally, a geopolymer artificial aggregate with a particle size of 4.75 to 26.5 mm and a water content of 17% is prepared.
[0087] 4) Maintenance and storage of materials after molding:
[0088] The formed materials are transported to a pile shed for curing and storage, wherein the temperature of the pile shed is controlled at 20°C and the humidity is controlled at 90%; the curing age is 28 days. After curing, geopolymer artificial aggregate is obtained.
[0089] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Method" (GB / T17431). After testing, the geopolymer artificial aggregate prepared in this embodiment has a 3d cylinder compressive strength of 13.28MPa, a 28d cylinder compressive strength of 17.03MPa, a 1h water absorption rate of 5.31%, and a softening coefficient of 0.83, and its performance meets the requirements of "Light Aggregate and Its Test Method" (GB / T17431).
[0090] Example 2
[0091] Use Figure 1 The process flow shown is for preparing geopolymer artificial aggregates:
[0092] 1) Pretreatment of phosphogypsum:
[0093] The phosphogypsum raw material (100 parts by weight of dihydrate phosphogypsum) is crushed and dispersed in a double-shaft mixer (the particle size of the crushed and dispersed phosphogypsum does not exceed 2.36 mm), and is evenly mixed with 2 parts by weight of a treating agent (lime and carbide slag, with a mass ratio of 1:1) to obtain a phosphogypsum treated material; the pH value of the phosphogypsum treated material is 12, and the specific surface area is 120.01 cm 2 / g.
[0094] 2) Preparation of geopolymer mixture:
[0095] 5 parts by weight of reinforcing agent (cement and lime, mass ratio of 1:1) and 95 parts by weight of auxiliary agent (slag) were added into a double-shaft screw mixer and mixed evenly to obtain a geopolymer mixture with a specific surface area of 320.40 cm 2 / g.
[0096] 3) Dispersible rubber powder incorporation and molding:
[0097] The phosphogypsum treated material and the geopolymer mixture are conveyed to a disc granulator in a mass ratio of 60:40, and the mixture is molded in the disc granulator (the disc inclination angle of the disc granulator is 55°); during the molding process, a dispersible rubber powder solution (mass concentration is 30%) is sprayed, and the mass ratio of the mixture after the phosphogypsum treated material and the geopolymer mixture are evenly mixed to the dispersible rubber powder solution is 105:2; finally, a geopolymer artificial aggregate with a particle size of 4.75 to 26.5 mm and a water content of 15.06% is prepared.
[0098] 4) Maintenance and storage of materials after molding:
[0099] The formed materials are transported to a pile shed for curing and storage, wherein the temperature of the pile shed is controlled at 20°C and the humidity is controlled at 80%; the curing age is 7 days. After curing, geopolymer artificial aggregate is obtained.
[0100] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Method" (GB / T17431). After testing, the geopolymer artificial aggregate prepared in this embodiment has a 3d cylinder compressive strength of 14.64MPa, a 7d cylinder compressive strength of 15.86MPa, a 1h water absorption rate of 2.38%, and a softening coefficient of 0.89, and its performance meets the requirements of "Light Aggregate and Its Test Method" (GB / T17431).
[0101] Example 3
[0102] The difference from Example 2 is:
[0103] In step 1), the phosphogypsum is selected from hemihydrate phosphogypsum, and the treating agent is cement; the pH value of the phosphogypsum treated material finally obtained is 11, and the specific surface area is 226.67 cm 2 / g.
[0104] In step 2), the reinforcing agent is lime and the auxiliary agent is phosphorus slag powder; the obtained geopolymer mixture has a specific surface area of 360.12 cm 2 / g.
[0105] The remaining steps and parameters are the same as those in Example 2 to obtain geopolymer artificial aggregate.
[0106] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Method" (GB / T17431). After testing, the geopolymer artificial aggregate prepared in this embodiment has a 3d cylinder compressive strength of 15.43MPa, a 28d cylinder compressive strength of 18.48MPa, a 1h water absorption rate of 1.57%, and a softening coefficient of 0.89, and its performance meets the requirements of "Light Aggregate and Its Test Method" (GB / T17431).
[0107] Example 4
[0108] The difference from Example 2 is:
[0109] In step 1), the phosphogypsum raw material (100 parts by weight of dihydrate phosphogypsum) is crushed and dispersed in a double-shaft mixer (the particle size of the crushed and dispersed phosphogypsum does not exceed 2.36 mm), and is uniformly mixed with 0.5 parts by weight of a treating agent (lime) to obtain a phosphogypsum treated material; the pH value of the phosphogypsum treated material finally obtained is 10, and the specific surface area is 117.41 cm 2 / g.
[0110] The remaining steps and parameters are the same as those in Example 2 to obtain geopolymer artificial aggregate.
[0111] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Method" (GB / T17431). After testing, the geopolymer artificial aggregate prepared in this embodiment has a 3d cylinder compressive strength of 9.82MPa, a 28d cylinder compressive strength of 11.68MPa, a 1h water absorption rate of 4.12%, and a softening coefficient of 0.81, and its performance meets the requirements of "Light Aggregate and Its Test Method" (GB / T17431).
[0112] Example 5
[0113] The difference from Example 2 is:
[0114] In step 2), the mass ratio of the reinforcing agent to the auxiliary agent is adjusted to 50:50; a geopolymer mixture is obtained with a specific surface area of 349.47 cm 2 / g.
[0115] The remaining steps and parameters are the same as those in Example 2 to obtain geopolymer artificial aggregate.
[0116] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Method" (GB / T17431). After testing, the geopolymer artificial aggregate prepared in this embodiment has a 3d cylinder compressive strength of 10.56MPa, a 28d cylinder compressive strength of 13.45MPa, a 1h water absorption rate of 3.29%, and a softening coefficient of 0.83, and its performance meets the requirements of "Light Aggregate and Its Test Method" (GB / T17431).
[0117] Example 6
[0118] The difference from Example 2 is:
[0119] In step 3), the mass ratio of the phosphogypsum treated material to the geopolymer mixture is modified to 90:10; finally, a geopolymer artificial aggregate with a particle size of 4.75 to 26.5 mm and a water content of 19.26% is prepared.
[0120] The remaining steps and parameters are the same as those in Example 2 to obtain geopolymer artificial aggregate.
[0121] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Method" (GB / T17431). After testing, the geopolymer artificial aggregate prepared in this embodiment has a 3d cylinder compressive strength of 11.75MPa, a 28d cylinder compressive strength of 14.46MPa, a 1h water absorption rate of 4.68%, and a softening coefficient of 0.83, and its performance meets the requirements of "Light Aggregate and Its Test Method" (GB / T17431).
[0122] Example 7
[0123] The difference from Example 2 is:
[0124] In step 4), the temperature of the curing and storage shed is controlled at 10°C and the humidity is controlled at 55%; the curing period is 15 days. After curing, the geopolymer artificial aggregate is obtained.
[0125] The remaining steps and parameters are the same as those in Example 2 to obtain geopolymer artificial aggregate.
[0126] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Method" (GB / T17431). After testing, the geopolymer artificial aggregate prepared in this embodiment has a 3d cylinder compressive strength of 9.14MPa, a 28d cylinder compressive strength of 10.56MPa, a 1h water absorption rate of 6.48%, and a softening coefficient of 0.81, and its performance meets the requirements of "Light Aggregate and Its Test Method" (GB / T17431).
[0127] Comparative Example 1
[0128] The difference from Example 7 is that:
[0129] In step 3), no dispersible rubber powder is added, and the specific steps are as follows:
[0130] The phosphogypsum treated material and the geopolymer mixture are conveyed to a disc granulator at a mass ratio of 70:30, and the mixture is formed in the disc granulator (the disc inclination angle of the disc granulator is 60°); finally, a geopolymer artificial aggregate with a particle size of 4.75 to 26.5 mm and a water content of 17.58% is prepared.
[0131] The remaining steps and parameters are the same as those in Example 7 to obtain geopolymer artificial aggregate.
[0132] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Methods" (GB / T17431). The test showed that the 3d cylinder compressive strength of the geopolymer artificial aggregate prepared in this comparative example was 6.64MPa, the 28d cylinder compressive strength was 9.36MPa, the 1h water absorption was 6.33%, and the softening coefficient was 0.74.
[0133] Comparative Example 2
[0134] The difference from Example 7 is that:
[0135] In step 3), the dispersible rubber powder solution is replaced with water; finally, a geopolymer artificial aggregate with a particle size of 4.75 to 26.5 mm and a water content of 18.21% is prepared.
[0136] The remaining steps and parameters are the same as those in Example 7 to obtain geopolymer artificial aggregate.
[0137] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Methods" (GB / T17431). The test showed that the 3d cylinder compressive strength of the geopolymer artificial aggregate prepared in this comparative example was 5.89MPa, the 28d cylinder compressive strength was 9.02MPa, the 1h water absorption rate was 9.05%, and the softening coefficient was 0.72.
[0138] Comparative Example 3
[0139] The difference from Example 7 is that:
[0140] Step 1) and step 2) are mixed together, and the specific steps are as follows:
[0141] D1) crushing and dispersing the phosphogypsum raw material (dihydrate phosphogypsum) in a double-shaft mixer (the particle size of the crushed and dispersed phosphogypsum does not exceed 2.36 mm), and uniformly mixing it with a treating agent (lime), a reinforcing agent (cement) and an auxiliary agent (slag and fly ash, with a mass ratio of 6:4) to obtain a mixed material; the mass ratio of the phosphogypsum raw material to the treating agent is 100:0.5; the mass ratio of the reinforcing agent to the auxiliary agent is 2:8; the total mass ratio of the phosphogypsum raw material and the treating agent to the total mass ratio of the reinforcing agent and the auxiliary agent is 70:30;
[0142] D2) molding the mixture in a disc granulator (the disc inclination angle of the disc granulator is 60°); during the molding process, spraying a dispersible rubber powder solution (mass concentration is 30%), the mass ratio of the mixture after the phosphogypsum treated material and the geopolymer mixture are evenly mixed to the dispersible rubber powder solution is 90:2; finally, a geopolymer artificial aggregate with a particle size of 4.75 to 26.5 mm and a water content of 16.86% is prepared.
[0143] D3) Maintenance and storage of materials after molding:
[0144] The formed materials are transported to a pile shed for curing and storage, wherein the temperature of the pile shed is controlled at 20°C and the humidity is controlled at 90%; the curing age is 28 days. After curing, geopolymer artificial aggregate is obtained.
[0145] The physical and mechanical properties of the prepared geopolymer artificial aggregate were tested according to "Light Aggregate and Its Test Methods" (GB / T17431). The test showed that the geopolymer artificial aggregate prepared in this comparative example had a 3d cylinder compressive strength of 7.26MPa, a 28d cylinder compressive strength of 9.58MPa, a 1h water absorption of 8.24%, and a softening coefficient of 0.72.
[0146] The description of the above embodiments is only used to help understand the method of the present invention and its core idea. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing geopolymer artificial aggregate, comprising the following steps: S1) mixing the crushed and dispersed phosphogypsum and the treating agent to obtain a phosphogypsum treated material; The reinforcing agent and the auxiliary agent are mixed to obtain a geopolymer mixture; S2) mixing the phosphogypsum treated material and the geopolymer mixture, and then molding; during the molding process, spraying a dispersible rubber powder solution; S3) curing the formed material to obtain geopolymer artificial aggregate.
2. The preparation method according to claim 1, characterized in that: The phosphogypsum includes at least one of dihydrate phosphogypsum and hemihydrate phosphogypsum; The treatment agent includes at least one of lime, carbide slag and cement; The mass ratio of the crushed and dispersed phosphogypsum to the treating agent is 100:0.5-2.
3. The preparation method according to claim 1, characterized in that: The pH value of the phosphogypsum treated material is 8-12, and the specific surface area is 100-400cm 2 / g.
4. The preparation method according to claim 1, characterized in that: The reinforcing agent includes cement and / or lime; The auxiliary agent includes at least one of industrial waste fly ash, slag and phosphorus slag powder; The mass ratio of the reinforcing agent to the auxiliary agent is 5-50:50-95.
5. The preparation method according to claim 1, characterized in that: The specific surface area of the geopolymer mixture is 200 to 400 cm 2 / g; The mass ratio of the phosphogypsum treated material to the geopolymer mixture is 50-90:10-50.
6. The preparation method according to claim 1, characterized in that: The forming is carried out in a disc granulator; the disc inclination angle of the disc granulator is 50° to 80°.
7. The preparation method according to claim 1, characterized in that: The mass concentration of the dispersible rubber powder solution is 20% to 45%; The mass ratio of the mixed material after the phosphogypsum treated material and the geopolymer mixed material is 90-105:0-10 to the dispersible rubber powder solution, and the mass of the dispersible rubber powder solution is not 0.
8. The preparation method according to claim 1, characterized in that: The particle size of the material after molding is 4.75-26.5 mm, and the water content is 15%-23%.
9. The preparation method according to claim 1, characterized in that: The curing temperature is 10-30° C., and the humidity is 50%-90%; and the curing period is 7-28 days. After the curing, storing; The storage temperature is 10-30° C., and the humidity is 50%-90%.
10. Geopolymer artificial aggregate obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
A hemihydrate phosphogypsum-based filler aggregate and its preparation method
CN113956011B
A green artificial aggregate based on phosphogypsum and preparation method thereof
CN115677306B
Phosphogypsum cementing material modifier and preparation method thereof, phosphogypsum cementing material and phosphogypsum lightweight aggregate
CN117229025A